A Wild Magcargo Appeared! - Chen, Yannic (Journal of Interdisciplinary Science Topics, 2017)
There are many Pokémon with unique characteristics that are not just impossible for a living organism but would have serious physical consequences. Magcargo is one such Pokémon that is being investigated in this paper. Its internal temperature of 18,000 °F would not only be extremely harmful to surrounding organisms, but a sudden appearance would most likely kill any person before they knew what had happened.